2017
DOI: 10.18227/1982-8470ragro.v11i4.4222
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de insetos fitófagos em Adenium obesum (Forssk.) Roem. & Schult no estado de Goiás

Abstract: Resumo: A rosa do deserto, Adenium obesum (Forssk.) Roem. & Schult, é uma planta ornamental da família Apocynaceae, de elevado valor comercial, que é empregada na ornamentação de jardins, praças e áreas públicas. A rápida expansão dessa espécie propiciou um ambiente favorável para sua colonização por diversas espécies de insetos e ácaros em novas regiões de introdução. Dessa forma, objetivou-se com este estudo relatar a ocorrência e injúrias ocasionadas por insetos fitófagos em A. obesum. Assim, foram realizad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Associated to that, the local meteorological conditions, already recorded at the experiment location (Monteiro Neto et al, 2018), favor more evapotranspiration chiefly due to high temperatures (Shimada et al, 2017), which must have increased water restriction to plants, which, according to Taiz and Zeiger (2013), affect all their development phases, limiting the growth of important physical characters like size, number of leaves, stem and branches, and may, therefore, make the plant more susceptible to attack by several phytophagous insects (Tiago Neto et al, 2017). With regard to the isolated effect of substrates, the compound containing OrganoAmazon ® and PuroHumus ® (S1) was the one that promoted most the development of desert rose seedlings, and was superior in all variables analyzed, including quality indices (Table 6).…”
Section: Use Of Hydrogel In Different Substrates For Production Of Dementioning
confidence: 99%
“…Associated to that, the local meteorological conditions, already recorded at the experiment location (Monteiro Neto et al, 2018), favor more evapotranspiration chiefly due to high temperatures (Shimada et al, 2017), which must have increased water restriction to plants, which, according to Taiz and Zeiger (2013), affect all their development phases, limiting the growth of important physical characters like size, number of leaves, stem and branches, and may, therefore, make the plant more susceptible to attack by several phytophagous insects (Tiago Neto et al, 2017). With regard to the isolated effect of substrates, the compound containing OrganoAmazon ® and PuroHumus ® (S1) was the one that promoted most the development of desert rose seedlings, and was superior in all variables analyzed, including quality indices (Table 6).…”
Section: Use Of Hydrogel In Different Substrates For Production Of Dementioning
confidence: 99%
“…For this specie, some insects as cochineals, aphids, caterpillar and thrips are the main pests. Neto et al (2017) reported and described some of these organisms found in 2012 when investigating A. obesum used in landscaping in Goias-Brazil. These authors identified two species of cochineals, Hemiberlesia rapax Comstock (Hemiptera: Diaspididae) and Parasaissetia nigra Nietner (Hemiptera: Coccoidea); and one oleander aphid Aphis nerii Boyer (Hemiptera: Aphididae), damaging the leaves, flowers and stem of A. obesum.…”
Section: Disease and Pestmentioning
confidence: 99%